OSH45, a homeobox transcription factor, coordinates low-phosphate adaptation in rice - Lu, Hong; Jin, Kangming; Luo, Yuelin; Wu, Yunrong; Liu, Yu; Xu, Jiming; Mao, Chuanzao (Frontiers in Plant Science, 2025)
Phosphorus (P), an essential macronutrient critical for plant growth and development, faces significant availability constraints in agricultural soils, substantially limiting crop yield potential. Transcription factors (TFs) play pivotal roles in phosphate (Pi) starvation responses in plants. In this study, we identified OSH45 (Oryza sativa homeobox 45), a homeobox domain TF in rice (Oryza sativa L.), which was strongly induced in roots under Pi starvation. Subcellular localization assays indicated that OSH45 is a nuclear localized protein. OSH45 overexpression transgenic plants exhibited enhanced low-Pi tolerance, characterized by significantly higher Pi concentrations and increased shoot and root biomass compared to wild type (WT) under Pi-limited conditions. Whereas osh45 loss-of-function mutants displayed no significant difference in shoot and root biomass compared to WT under both Pi-sufficient and Pi-limited conditions, but showed lower Pi concentration under Pi-sufficient conditions. Through transcriptomic profiling, 2,406 differential expressed genes (DEGs) were identified in OSH45 overexpression plants versus WT under Pi-sufficient conditions. About 38% of Pi starvation-induced (PSI) genes were upregulated and 25% of Pi starvation-suppressed (PSS) genes were downregulated in OSH45 overexpression plants. The expression of phosphate transporters, such as OsPT1, OsPT2, OsPT4, OsPT8, and acid phosphatases was upregulated, while the expression of Pi signaling repressors OsSPX1-3 was suppressed in OSH45 overexpression plants. Conversely, osh45 displayed decreased expression of OsPT1 and OsPT8 compared to WT. Altogether, our findings demonstrated that OSH45 is a novel TF involved in Pi deficiency response, regulating a set of Pi starvation responsive (PSR) genes to optimize plant adaptation to Pi-limited environments. This mechanism provides a strategic target for engineering Pi-efficient crops.